Online Schooling versus Offline Schooling: An Effectiveness Assessment (Bangladesh Journal of Public Administration, 2022)
The COVID 19situations became a worldwide health issue at the very beginning of the year 2020 and has formed a public health emergency of global concern. Thus online schooling has gained popularity and itspractice has increased amazingly. The coronavirus situation not only made online education more crucial and urgent, but also gave scope fora thorough discussion on the subject. The purpose of this study is to knowwhich one is more effective between online schooling and offlineschooling and also to learn the limitation of these two schooling systems. A total of 56 students of K.M.Latif Institutions, Mathbaria in class x(section “A”) were attending a mathematical class where 28 of them were in the classroom with the teacher and 28 of them were attended online using the Zoom apps facility at the same time as requested. After one hour of class, a test was held between two groups. According to the study's findings, both offline and online schooling methods are effective under different circumstances. The study has found that despite somelimitations online schooling method is preferable at least in pandemic or emergency situations. But both schooling systems have advantages and disadvantages of their own. And it is also predicted that in the age of 4th IR, we cannot deny the blessing of technology. Thus online schoolin method has become increasingly popular in recent days.